EVALUATION OF THE QUALITY OF FINANCIAL STRATEGY (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
The financial strategy of any organization is a system of long-term goals of financial activity, which represents its financial ideology, as well as the most effective ways to achieve these goals. Financial strategy development is an area of financial planning. As part of the organization's overall strategy, it should be consistent with its goals and direction. Formulation of financial strategy, qualitative research and necessary adjustments are relevant for organizations of any size and type, for any market sector, for both state and municipal enterprises, public organizations and commercial firms. Assessment of the quality of the financial strategy and the compliance of the strategy with the planned goals is an urgent issue for research.